ANALISIS PENGARUH BENTUK SERAMBI MASJID TERHADAP KENYAMANAN TERMAL ADAPTIF - Qodir, Abdul; Setyowati, Erni; Suryono, Suryono (Prodi Arsitektur UNIVERSITAS KEBANGSAAN, 2020)
This study examines the effect of the porch on the adaptive thermal comfort of mosques by taking 2 mosques that have different porch shapes with the specific purpose of obtaining data on the neutrality, acceptability and preferences of the mosque respondents' thermal conditions in the framework of developing adaptive thermal comfort standards for Indonesia. Measurement of physical environment variables is done by taking data on temperature, humidity, air velocity, and mean radiant temperature (MRT) at 2 mosques and at the same time the impression and thermal preference questionnaire data are taken, examination of clothing types and activities, and list of thermal environment controls to 40 respondents in each mosque. Data of thermal neutrality and thermal preferences were analyzed by regression analysis using SPSS 19 software, while thermal acceptance was analyzed based on the results of the questionnaire answers. The analysis showed that the neutrality value at Ulul Albab mosque was Tdb = 28.47 OC, ET * = 30.11 OC, SET * = 23.11 OC, TSENS = 1.17, DISC = -1.06, and PMV = -0.65, this data shows that the neutral condition desired by respondents is slightly below the average condition, while the neutrality in Nurul Ilmi mosque at Tdb = 30.27 OC, ET * = 31.65 OC, SET * = 29.05 OC, TSENS = 1.03, DISC = 1.68, and PMV = 1.22, this data also shows that the neutral conditions desired by respondents are slightly below average conditions. While the preference value at Ulul Albab mosque is Tdb = 22.25 OC, ET * = 28.62 OC, SET * = 24.24 OC, TSENS = 0.23, DISC = 0.23, and PMV = -0.60 and preference conditions at Nurul Ilmi mosque at Tdb = 29.11 OC, ET * = 31.17 OC, SET * = 28.50 OC, TSENS = 1.04, DISC = 1.45, and PMV = 1.03. As many as 92% of respondents in the Ulul Albab mosque can accept local thermal conditions in the temperature range of 27oC - 31oC. While 90% of respondents in the Nurul Ilmi mosque can accept local thermal conditions in the temperature range of 27oC-32oC. The results of the neutrality, acceptance and preference analysis show that the Ulul Albab mosque is better than the Nurul Ilmi mosque.